ANALYSIS OF ADVERSE EVENTS AFTER IMMUNIZATION WITH VACCINES AGAINST Sars-Cov-2 (World Science, 2021)
Although the WHO-recommended coronavirus vaccines are safe and effective, vaccines provide new information to healthcare professionals about the extent and nature of adverse reactions to these drugs. The aim of the study is supplementing the available data on adverse reactions of vaccines on the example of the experience of vaccination of the teaching staff of the Cherkasy Medical Academy with vaccines COVISHIELD and COMIRNATY. Information for this study was collected retrospectively through a survey of 72 employees of the Cherkasy Medical Academy who were vaccinated with the COVISHIELD vaccine (first dose); 67 workers vaccinated with AstraZeneca (second dose); 54 workers who were vaccinated with COMIRNATY vaccine (first dose); 52 people vaccinated with this vaccine (second dose). The study confirmed that among the local side effects, the most common were pain at the injection site, among the systemic - fever, weakness, fatigue and drowsiness, headache, muscle pain, chills. Most of the side effects were most pronounced in young people, more often in women than in men.